Role of Calcium-independent Phospholipase A(2)β in High Glucose-induced Activation of RhoA, Rho Kinase, and CPI-17 in Cultured Vascular Smooth Muscle Cells and Vascular Smooth Muscle Hypercontractility in Diabetic Animals - Xie, Zhongwen (American Society for Biochemistry and Molecular Biology, 2010)
Previous studies suggest that high glucose-induced RhoA/Rho kinase/CPI-17 activation is involved in diabetes-associated vascular smooth muscle hypercontractility. However, the upstream signaling that links high glucose and RhoA/Rho kinase/CPI-17 activation is unknown. Here we report that calcium-independent phospholipase A(2)β (iPLA(2)β) is required for high glucose-induced RhoA/Rho kinase/CPI-17 activation and thereby contributes to diabetes-associated vascular smooth muscle hypercontractility. We demonstrate that high glucose increases iPLA(2)β mRNA, protein, and iPLA(2) activity in a time-dependent manner. Protein kinase C is involved in high glucose-induced iPLA(2)β protein up-regulation. Inhibiting iPLA(2)β activity with bromoenol lactone or preventing its expression by genetic deletion abolishes high glucose-induced RhoA/Rho kinase/CPI-17 activation, and restoring expression of iPLA(2)β in iPLA(2)β-deficient cells also restores high glucose-induced CPI-17 phosphorylation. Pharmacological and genetic inhibition of 12/15-lipoxygenases has effects on high glucose-induced CPI-17 phosphorylation similar to iPLA(2)β inhibition. Moreover, increases in iPLA(2) activity and iPLA(2)β protein expression are also observed in both type 1 and type 2 diabetic vasculature. Pharmacological and genetic inhibition of iPLA(2)β, but not iPLA(2)γ, diminishes diabetes-associated vascular smooth muscle hypercontractility. In summary, our results reveal a novel mechanism by which high glucose-induced, protein kinase C-mediated iPLA(2)β up-regulation activates the RhoA/Rho kinase/CPI-17 via 12/15-lipoxygenases and thereby contributes to diabetes-associated vascular smooth muscle hypercontractility.